On the use of discontinuous nonlinear bistable dynamics to increase the responsiveness of energy harvesting devices. (September 2017) - Radice, Joshua J.; Ellsworth, Phillip J.; Romano, Michael A.; Lazarus, Nathan; Bedair, Sarah S.
Highlights: Discontinuous Nonlinear Bistable equations of motion derived. A proxy Discontinuous Nonlinear Bistable system is parametrically studied. Discontinuous Nonlinear Bistable structures require less excitation than continuous bistable devices to reach the preferred large-amplitude motion for energy harvesting applications. Discontinuous Nonlinear Bistable structures respond to a broader excitation frequencies than continuous bistable devices. Abstract: There is promise in the use of bistable devices to transduce ambient vibrations into electrical power. However, it is critical to sustain the relatively large amplitude snap-through motion, or interwell motion, to significantly improve the responsiveness of bistable devices as compared to linear resonance-based approaches. This work posits that relatively stiff structural elements can be placed in the vicinity of the equilibria of bistable devices such that the discontinuous change in dynamics will tend to eject an otherwise small amplitude motion into the large amplitude interwell orbit that is to be preferred for energy harvesting applications. The discontinuous nonlinear dynamic equations of motion are derived and a proxy system parametrically studied. These numerical studies demonstrate that discontinuous nonlinear bistable devices have a significantly broadened frequency range that elicits the large amplitude snap through behavior. It is also seen that interwell motion is achievable at significantly reduced excitation amplitudes through these discontinuous structural elements.